Semiotics of destruction: traces on the environment. (May 2022) - Björkvall, Anders; Archer, Arlene
Research in fields such as multimodality and semiotics has focused on creation of value in different forms: aesthetic, economic and symbolic. However, the destruction of value has attracted much less attention. The aim of this article is to identify social, semiotic and ideological functions of acts of destruction based on an analysis of the traces these acts leave on the urban environment. Five overarching acts of destruction are discussed, but the authors' main focus is on what they call transformation-driven and social presence-driven destruction, with two examples from Sweden and South Africa. The article discusses sanctioned destructive acts that are largely in compliance with dominating semiotic regimes at a certain time and place, as well as disruptive actions that challenge or even disobey those regimes. The analysis shows how a distinction between sanctioned and disruptive is in no way clear and often depends on complex power distributions between semiotic regimes at a given time and place. In fact, traces in the physical environment that may point to or index highly destructive acts can, in relation to other semiotic regimes, be regarded as creative and constructive. The authors argue that the semiotic processes of destruction and the traces they leave deserve more attention from research in the fields of multimodality and semiotics.